Design and Development of A Portable Conductivity-Based Salinity Measurement System for Coastal Well Water - Azhari, Mohammad Rasyidi; Hudha, Lalu Sahrul; Kurniawidi, Dian Wijaya (Universitas Islam Negeri (UIN) Mataram, 2024)
Seawater intrusion increases groundwater salinity and affects the quality of residents' healthy water around coastal areas. Therefore, simple mapping of seawater intrusion distribution based on the salinity values of healthy water around coastal areas is necessary. This mapping can be done by measuring the salinity of the water using a portable and real-time instrument. The existing measurement system is not resistant to corrosion, does not have a data logger system, and does not have a display system capable of showing real-time salinity value graphs. In this study, a portable salinity measurement system resistant to corrosion caused by high salt levels was developed. The salinity measurement method used is the conductivity method. The salinity value of the solution is proportional to the measured conductivity value of the solution. Conductivity measurement uses two electrodes connected to a voltage divider circuit with an AC power source to avoid electrode polarization and electrochemical reactions. The output voltage of this voltage divider circuit is proportional to the conductivity value of the solution in which the two electrodes are immersed, based on Ohm's law. This output voltage is fed into a signal conditioning circuit consisting of an amplifier, filter, and full-wave rectifier. Subsequently, an Atmega 328 microcontroller processes this data for real-time display on a TFT LCD and real-time storage on a data logger module. Testing and calibration are then carried out to obtain the relationship between the solution's salinity value and the measured output voltage, expressed as a 2nd-order polynomial function Vout = -0.0012C2 + 3.5126C + 14.194. Additionally, it is known that salinity measurement results using the conductivity method are influenced by temperature, so temperature measurement using the DS18B20 sensor is required to obtain a compensation factor due to temperature changes. The higher the temperature, the higher the measured salinity value for the exact solution measurement.